Computed Tomographic Measurements of the Sulcus Angle of the Femoral Trochlea in Small-Breed Dogs with and without Medial Patellar Luxation - Sasaki, Akari; Hidaka, Yuki; Mochizuki, Manabu; Honnami, Muneki (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Trochleoplasty is often performed in dogs with medial patellar luxation (MPL); however, the current guidelines on when to perform a trochleoplasty in dogs are vague. The sulcus angle (SA) is used to assess the femoral trochlear morphology in humans. The aim of this study is to describe a method to measure the SA and other parameters of trochlea morphology in dogs using computed tomography. First, we searched for a suitable measuring location for the SA. Transverse images of the femurs were obtained as perpendicular planes to the tangent of the femoral trochlea which was 0 to 60 degrees (every 5 degrees) to the anatomical axis of the femur. The deepest point of the femoral trochlea was found in the transverse images perpendicular to the tangent of the femoral trochlea which was at 15 degrees to the anatomical axis of the femur. The SA and the other parameters of femoral trochlea morphology were measured at the deepest point of the femoral trochlea. The SA of the stifle joints with grade 3 and 4 MPL was significantly higher than the SA of stifle joints not affected by MPL. There was no significant difference in the SA between dogs affected by grade 1 and 2 MPL and dogs not affected by MPL. Further studies are needed to establish whether the SA can be used as selection criteria for trochleoplasty.
Keywords: sulcus angle; dogs; femoral trochlea; patellar luxation; computed tomography